Adsorption orientation control of porphyrin on titania-nanosheet. Issue 46 (12th November 2020) - Tominaga, Shota; Sano, Keito; Hirade, Yugo; Shimada, Tetsuya; Ishida, Tamao; Takagi, Shinsuke
Graphical abstract: Adsorption orientation of porphyrin on titania nanosheet. Highlights: The adsorption orientation of porphyrin on the titania nanosheet (TNS) was examined. The adsorption orientation angle was quantitatively evaluated by dichroic waveguide spectroscopy. The adsorption angle of organic molecules can be controlled on TNS surface by changing the solvent environments. Abstract: In this study, cis -di( N -methyl-2-pyridine)-diphenyl porphyrin ( cis -DMPyP 2+) was adsorbed on titania-nanosheet (TNS, Ti0.89 □0.11 O2.00 0.11− (□: vacant)) monolayer film prepared by Langmuir-Blodgett method. The adsorption behavior such as maximum adsorption density and adsorption orientation change behavior of cis -DMPyP 2+ were examined by absorption and dichroic waveguide spectroscopy, respectively. By the adsorption on TNS, the maximum absorption wavelength (λmax ) of cis -DMPyP 2+ shifted from 421 to 456 nm in water. The maximum adsorption amount without aggregation was ca. 100% vs . cation exchange capacity of TNS. The orientation angle of cis -DMPyP 2+ on TNS in water was less than 5°, that is porphyrin plane was almost parallel to the TNS surface. On the other hand, λmax of cis -DMPyP 2+ on TNS was 429 nm in ethanol. The adsorption orientation angle of cis -DMPyP 2+ on TNS in ethanol was turned out to be 45°. These results indicate that the adsorption orientation angle of cis -DMPyP 2+ depends on the solvent. It was demonstrated that the adsorption angle of organic molecules can be controlled on TNS surface by changing the solvent environments.